International Trade in Variety and Domestic Production - Ulf Lewrick; Lukas Mohler; Rolf Weder (University of Basel, Center of Business and Economics (WWZ), 2011)
Welfare gains from increasing product variety are an important source of the gains from international trade. Recent empirical studies have largely focused on measuring the gains from an increased variety of imports. Trade theory, however, suggests that international trade heavily affects the variety of domestically produced goods as well. To overcome the typical data limitations on domestic varieties, we employ the number of domestic establishments as a proxy of the number of domestic varieties and include information on business dynamics to assess the importance of new and disappearing varieties. Our results suggest that for U.S. manufacturing, losses in domestic varieties from 1992 to 2006 are substantial and outweigh the gains from increased imported varieties.
Keywords: F10; F12; F14; 330; Variety gains; margins of trade; lambda ratio; U.S. manufacturing; Produktdifferenzierung; Handelseffekt; Exportpreis; Außenhandelssektor; Theorie; USA